Cover Picture: Single Crystals Popping Under UV Light: A Photosalient Effect Triggered by a [2+2] Cycloaddition Reaction (Angew. Chem. Int. Ed. 23/2014). Issue 23 (22nd April 2014) - Medishetty, Raghavender; Husain, Ahmad; Bai, Zhaozhi; Runčevski, Tomče; Dinnebier, Robert E.; Naumov, Panče; Vittal, Jagadese J.
<x xml:space="preserve">Abstract</x> The self‐propulsion of single crystals of three Zn(II) complexes under UV light is described by P. Naumov, J. J. Vittal et al. in their Communication on page 5907 ff. This visually impressive dynamic behavior is a consequence of the accumulation and sudden release of strain created by crystal expansion following the formation of 1D coordination polymers by a [2+2] cycloaddition reaction. Understanding this effect, which is mechanistically analogous to the bursting of popcorn in a hot pan, may help in the design of new light‐driven mechanical actuators.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>